Der angebliche Bericht über die Umschiffung Afrikas. Eine wissenschaftsgeschichtliche Einordnung - Gertzen, Thomas L. (Zeitschrift für ägyptische Sprache und Altertumskunde, 2010)
Based on the examination of archival material from the Erman correspondence, stored at the State and University Library Bremen and the Royal Museums of Art and History in Brussels, as well as on contemporary and recent publications, this article is to present the affair of the forged scarabs of Necho relating to the alleged circumnavigation of Africa, discredited by the representatives of the 'Berlin School′, on the basis of a thorough linguistic analysis and thereby constituting a 'paradigm′ in Egyptology.